2017
DOI: 10.1080/1828051x.2017.1401438
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene affects the immune responses of finishing pigs

Abstract: The objective of this study was to evaluate dietary lycopene levels on the immune responses of finishing pigs. Forty barrows and 40 gilts, averaging 75.04 ± 1.6 kg of initial weight, were allotted in a randomised blocks design arranged in a 2 Â 5 factorial scheme, consisting of two sexes (males and females) and five lycopene levels (0, 12.5, 25.0, 37.5, 50.0 mg/kg of diet). The studied parameters were submitted to the statistical analysis adopting 5% significance. Increasing lycopene in pig diets increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Regarding to Leukogram in our study LYC treated group (group 2) revealed significant leukocytosis and lymphocytosis 4 days PI. Similar results were obtained by Fachinello et al (2018), who observed the immuneactivating effect of LYC on finishing pigs. In contrast to our results Pozzo et al (2013) found that male Hubbard broiler chicks received the basal diet supplemented with 500 mg LYC/kg for 35 days didn't showed any significant changes in leukogram.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding to Leukogram in our study LYC treated group (group 2) revealed significant leukocytosis and lymphocytosis 4 days PI. Similar results were obtained by Fachinello et al (2018), who observed the immuneactivating effect of LYC on finishing pigs. In contrast to our results Pozzo et al (2013) found that male Hubbard broiler chicks received the basal diet supplemented with 500 mg LYC/kg for 35 days didn't showed any significant changes in leukogram.…”
Section: Discussionsupporting
confidence: 89%
“…Increase TLC and lymphocytic count may be attributed to that LYC stimulates lymphocytes by increasing the production of interleukin-2 and interferon gamma, a potent activator of T lymphocytes (Yuksek et al, 2013). Also, LYC stimulate leukocytic proliferation and synthesis (Fachinello et al, 2018). VE treated E. coli infected group (group 6) when compared to infected non-treated group showed a significant decrease in heterophils and monocytic count 4 days and 2 weeks PI respectively (restoration of their values toward control limits).…”
Section: Discussionmentioning
confidence: 91%
“…This suggests that the effect of lycopene in immune system modulation is not as simple as absorption and execution and it could be a result from a complicated network consisted of simultaneous activation of various immunomodulatory pathways [99]. In barrow and gilt finishing pigs, 0, 12.5, 25, 37.5, 50 mg/kg of lycopene administration followed by immunization using 1 mg BSA caused increased lymphocyte concentration and anti-BSA IgG, reduced neutrophil concentration and eosinophil while causing no change in basophil and monocyte [100]. Changes in lymphocyte concentration could be an indicator of activation of cell-mediated or humoral immune response and thus, lycopene was proposed to be able to influence immune response and the production of antigen-specific antibodies.…”
Section: Immunomodulatory Effects Of Lycopenementioning
confidence: 99%
“…Patients with type 2 diabetes mellitus (T2DM) experience disorders of blood glucose metabolism that affect immunity. It has been found that diabetes mellitus (DM) patients experience disturbances in the number and function of neutrophils (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%